The Effect of Tofu Liquid Waste and Organic Mulch on the Growth of Cocoa (Theobroma Cacao L.) Nursery Plants in a Polybag - Ifan Aulia Candra; Eri Samah (Journal of Applied Agricultural Science and Technology, 2022)
This study aims to examine the influence of the concentration level of organic tofu liquid waste and rice straw mulch on the growth of cacao (Theobroma cacao L) seedlings. It was carried out using three variables, namely the concentration of tofu liquid waste and four treatment levels. These include treatments without tofu liquid waste 0 ml/kg/plant (T0), and with 60 ml/kg/plant (T1), 80 ml/kg/plant (T2), and 100 ml/kg/plant (T3), respectively. Furthermore, rice straw organic mulch factor with three levels, namely 15 gr/plant (15 tons/ha) (M1), 20 gr/plant (20 tons/ha) (M2), and 25 gr/plant (25 tons/ha) (M3) was also used. The results indicated that the concentration of liquid organic fertilizer derived from tofu liquid waste significantly affected plant height at the age of 3 months. The tallest plant measured 64.78 cm in height, with 21.33 leaves, stem diameter of 0.72, and leaf area of 17.58 cm2. Organic rice straw mulch did not have a significant effect on all plant factors. This showed that the application of liquid organic fertilizer tofu waste influences plant height, leaf number, and stem diameter, and there is no effect on the leaf surface, while rice straw mulch did not alter all plant variables.